When Will Collective Action Be Effective? Violent and Non-Violent Protests Differentially Influence Perceptions of Legitimacy and Efficacy Among Sympathizers. (February 2014) - Thomas, Emma F.; Louis, Winnifred R.
Collective action will be effective in achieving broader social change goals to the extent that it influences public opinion yet the degree to which collective action "works" in changing opinion is rarely studied. Experiment 1 ( n = 158) showed that, consistent with a logic of strategic non-violence, non-violent collective action more effectively conveys a sense of the illegitimacy of the issue and the efficacy of the group, thereby promoting support for future non-violent actions. Experiment 2 ( n = 139) explored the moderating role of allegations of corruption. A social context of corruption effectively undermined the efficacy and legitimacy of non-violent collective action, relative to support for violence, thereby promoting (indirectly) support for future extreme action. The implications of this research, for the logic of strategic non-violence and mobilizing supportive public opinion, are discussed.